2021
DOI: 10.1136/bmjebm-2021-111724
|View full text |Cite
|
Sign up to set email alerts
|

Ivabradine added to usual care in patients with heart failure: a systematic review with meta-analysis and trial sequential analysis

Abstract: ObjectivesTo assess the beneficial and harmful effects of adding ivabradine to usual care in participants with heart failure.DesignA systematic review with meta-analysis and trial sequential analysis.Eligibility criteriaRandomised clinical trials comparing ivabradine and usual care with usual care (with or without) placebo in participants with heart failure.Information sourcesMedline, Embase, CENTRAL, LILACS, CNKI, VIP and other databases and trial registries up until 31 May 2021.Data extractionPrimary outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
6
0
1
Order By: Relevance
“…In the summary analysis, there was no noteworthy discrepancy observed between the results of the mega-trials and those of smaller trials (summary ROR 1.00, 95% confidence interval [CI] 0.97-1.04; I 2 =0.0, P-value for heterogeneity=0.478; Figure 2). In two instances when comparing ivabradine to placebo and new adenosine diphosphate receptor agonist versus clopidogrel, the disagreement between the mega-trials and the respective smaller trials was beyond chance (ROR 1.21, 95% CI, 1.0-1.47 and ROR 0.83, 95% CI, 0.73, 0.95, respectively) [21, 22].…”
Section: Resultsmentioning
confidence: 99%
“…In the summary analysis, there was no noteworthy discrepancy observed between the results of the mega-trials and those of smaller trials (summary ROR 1.00, 95% confidence interval [CI] 0.97-1.04; I 2 =0.0, P-value for heterogeneity=0.478; Figure 2). In two instances when comparing ivabradine to placebo and new adenosine diphosphate receptor agonist versus clopidogrel, the disagreement between the mega-trials and the respective smaller trials was beyond chance (ROR 1.21, 95% CI, 1.0-1.47 and ROR 0.83, 95% CI, 0.73, 0.95, respectively) [21, 22].…”
Section: Resultsmentioning
confidence: 99%
“…Authors showed that ivabradine does not affect the risks of all-cause death and CV death in patients with HF (regardless of LVEF). Furthermore, the effect of ivabradine on HRQoL was found to be small and potentially without relevance to patients [ 74 ]. A review by Benstoem et al [ 75 ] conducted two meta-analyses on individuals with HFrEF who underwent long-term treatment with ivabradine.…”
Section: Discussionmentioning
confidence: 99%
“…Si bien se habría demostrado, mediante el estudio SHIFT disminución de mortalidad cardiovascular, metaanálisis de los ensayos para ivabradina (BEAUTIFUL y SHIFT) no lograron demostrar disminución significativa de la mortalidad global ni por eventos cardiovasculares. Por su mecanismo de acción, los principales efectos adversos son bradicardia, bloqueos auriculoventriculares y síncope (40,41) .…”
Section: Terapias Para Icunclassified